Retrospective cohort-based comparison of intraoperative liposomal bupivacaine versus bupivacaine for donor site iliac crest analgesia during alveolar bone grafting. Issue 12 (December 2019) - Patel, Ronak A.; Jablonka, Eric M.; Rustad, Kristine C.; Pridgen, Brian C.; Sorice-Virk, Sarah S.; Borrelli, Mimi R.; Khosla, Rohit K.; Lorenz, H. Peter; Momeni, Arash; Wan, Derrick C.
Summary: Introduction: Bone grafting of alveolar clefts is routinely performed with cancellous bone harvested from the iliac crest. Graft site morbidity is frequently seen, with early postoperative pain being one of the most common complaints. Liposomal bupivacaine (LB) has been demonstrated to provide improvement in postoperative pain for patients undergoing bunionectomy or hemorrhoidectomy, which may translate to patients requiring iliac crest bone graft harvest. Methods: Thirty-eight patients undergoing iliac crest bone harvest were included in the study. Twenty-one patients underwent open iliac crest bone graft harvest with administration of 0.25% bupivacaine at the hip donor site, while 17 patients received local infiltration of 1.3% liposomal bupivacaine. Patient-reported pain scores, total narcotic use, length of stay, and postoperative steps were monitored. Results: There were no significant differences in age, weight, distribution of clefts, or choice of donor hip between the two groups. There were no significant differences in length of hospitalization stay. However, differences were noted in average postoperative pain scores at five of six time points in the first 24 h, total oral morphine equivalents administered (4.7 ± 5.3 vs. 14.3 ± 12.0), and steps at postoperative days one to three ( p  < 0.001, for all three days) for patients receiving 1.3% LB versus 0.25% bupivacaine, respectively. Conclusion: Reduced pain scores and increased postoperative activity highlight the potential of LB to improve postoperative pain management in children undergoing iliac crest bone harvest for alveolar bone grafting.